2022
DOI: 10.1371/journal.pone.0263716
|View full text |Cite
|
Sign up to set email alerts
|

The impact of risk perceptions and belief in conspiracy theories on COVID-19 pandemic-related behaviours

Abstract: Throughout the COVID-19 pandemic, conspiracy theories about the virus spread rapidly, and whilst governments across the globe put in place different restrictions and guidelines to contain the pandemic, these were not universally adhered to. This research examined the association between pandemic related risk perceptions, belief in conspiracy theories, and compliance with COVID-19 public guidelines amongst a UK sample (n = 368). Participants rated their level of concern for a series of potential risks during th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 90 publications
3
21
1
2
Order By: Relevance
“…Our findings reiterate past work that supports a conspiratorial mindset, suggesting that people who endorse some conspiracies tend to validate multiple other conspiracies (Brotherton et al, 2013;Bruder et al, 2013). As such conspiratorial beliefs tend to be unchanging in nature (Kroke & Ruthig, 2022) and can affect health behaviors, this finding has serious implications including reduced support for health-protective behaviors (Allington et al, 2021;Bierwiaczonek et al, 2020;Uscinski et al, 2020), non-compliance with public health guidelines and policies (Pummerer et al, 2022), reduced risk perceptions (Hughes et al, 2022), and increased use of alternative medicine (Oliver & Wood, 2014).…”
Section: Conspiratorial Thinkingsupporting
confidence: 81%
“…Our findings reiterate past work that supports a conspiratorial mindset, suggesting that people who endorse some conspiracies tend to validate multiple other conspiracies (Brotherton et al, 2013;Bruder et al, 2013). As such conspiratorial beliefs tend to be unchanging in nature (Kroke & Ruthig, 2022) and can affect health behaviors, this finding has serious implications including reduced support for health-protective behaviors (Allington et al, 2021;Bierwiaczonek et al, 2020;Uscinski et al, 2020), non-compliance with public health guidelines and policies (Pummerer et al, 2022), reduced risk perceptions (Hughes et al, 2022), and increased use of alternative medicine (Oliver & Wood, 2014).…”
Section: Conspiratorial Thinkingsupporting
confidence: 81%
“…The widespread prevalence of conspiracy beliefs was manifested amid the COVID-19 pandemic with suggested negative psychological, social, and health impacts [ 59 , 60 , 61 ]. Specifically, our previous research has shown that the belief in the manmade origin of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), and the endorsement of the notion that COVID-19 is part of a biologic warfare, was associated with higher anxiety levels among the general public and among university students in Jordan [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that health-related CBs can lower health-seeking intentions ( Natoli and Marques, 2021 ). In many studies, anti-COVID-19 health protective attitudes and behavior were negatively related to COVID-19 CBs ( Biddlestone et al, 2020 ; Bierwiaczonek et al, 2020 ; Earnshaw et al, 2020 ; Egorova et al, 2020 ; Kowalski et al, 2020 ; Rieger, 2020 ; Romer and Jamieson, 2020 ; Abadi et al, 2021 ; Allington et al, 2021 ; Farias and Pilati, 2021 ; Karić and Međedović, 2021 ; Resnicow et al, 2021 ; Soveri et al, 2021 ; Chayinska et al, 2022 ; Latkin et al, 2022 ; Pavela Banai et al, 2022 ; Garry et al, 2022 ; Hughes et al, 2022 ; Pummerer et al, 2022 ) and conspiracy mentality ( Gualda et al, 2021 ; Oleksy et al, 2021a ; Pellegrini et al, 2021 ; Plohl and Musil, 2021 ; Maftei and Holman, 2022 ). However, sometimes no relationship ( Prichard and Christman, 2020 ; Alper et al, 2021 ; Naveed et al, 2021 ; Schnell et al, 2021 ; Šuriņa et al, 2021 ; Yarosh et al, 2021 ) or even positive relationships ( Alper et al, 2021 ; Corbu et al, 2021 ; Wang and Kim, 2021 ) between these variables were reported.…”
Section: Resultsmentioning
confidence: 99%